Postural Changes During Exteroceptive Thin Plantar Stimulation: The Effect of Prolonged Use and Different Plantar Localizations - Tramontano, Marco; Piermaria, Jacopo; Morone, Giovanni; Reali, Alice; Vergara, Martin; Tamburella, Federica (Frontiers in Systems Neuroscience, 2019)
Somatosensory information arising from the foot has an important role in posture as well as visual and vestibular cues.. Our hypothesis is that the effects of prolonged stimulation are greater than those of short stimulation and that varying the plantar location can affect postural control. Forty healthy participants were recruited and randomly assigned to four different plantar location groups: Lateral Insert (LI), Medial Insert (MI), Disharmonious Insert (DI) and Central Insert (CI). An instrumental assessment was performed before the plantar stimulation (T0), immediately after the positioning of the inserts (T1) and after seven days of daily stimulation (T7). A follow-up was performed 15 days after (T15). The following stabilometric parameters were considered for both open eyes (OE) and closed eyes (CE) conditions: length of the sway (L) of the Center of Pressure (CoP); CoP maximum movements in the medio-lateral (X) and antero-posterior directions (Y). Comparing the effects of different plantar insert locations, the MI and CI groups were significantly different in the follow-up measures at T15, specifically for closed eyes measures. When we compared measures across time within each location group, CI group increased measures of X and Y data at T7 compared to other assessment times (T0, T1 and T15). In both MI and LI groups, L was significantly reduced, and X significantly increased at the T7 assessment compared to the T0, T1 and T15 assessments. The prolonged use of exteroceptive plantar stimulation and the location of plantar inserts may have a role to reshape postural control.